2019
DOI: 10.1111/jocn.14839
|View full text |Cite
|
Sign up to set email alerts
|

New graduate nurses’ understanding and attitudes about patient safety upon transition to practice

Abstract: Aims To explore the transition experiences of newly graduated registered nurses with particular attention to patient safety. Background New graduate registered nurses’ transition is accompanied by a degree of shock which may be in tune with the described theory–practice gap. The limited exposure to clinical settings and experiences leaves these nurses at risk of making errors and not recognising deterioration, prioritising time management and task completion over patient safety and care. Design Qualitative des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
(52 reference statements)
1
52
0
1
Order By: Relevance
“…The key to maintaining patient safety lies in establishing a safety culture. Murray et al pointed out that the medical staff's safety attitudes toward patients are vital in the patient safety culture, and improved medical staff's attitudes to patient safety promote patient health and safety [ 9 ]. Haugen et al also proposed that the attitude and behavior of the surgical team reflected the development of safety procedures in the operating room [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key to maintaining patient safety lies in establishing a safety culture. Murray et al pointed out that the medical staff's safety attitudes toward patients are vital in the patient safety culture, and improved medical staff's attitudes to patient safety promote patient health and safety [ 9 ]. Haugen et al also proposed that the attitude and behavior of the surgical team reflected the development of safety procedures in the operating room [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is concerning that research has shown that medication errors are frequent among nurses with less than five years of experience (Makary & Daniel, 2016; Treiber & Jones, 2018). It has also been reported that NGRNs experience the administration of medication as causing stress (Murray, Sundin, & Cope, 2019). Among NGRNs, medication errors are related to nursing care with heavy patient workloads and patients with complex medical diagnoses (Saintsing, Gibson, & Pennington, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is concerning that research has shown that medication errors are frequent among nurses with less than five years of experience (Makary & Daniel, 2016;Treiber & Jones, 2018). It has also been reported that NGRNs experience the administration of medication as causing stress (Murray, Sundin, & Cope, 2019).…”
Section: Need For Further Trainingmentioning
confidence: 99%
“…Being in a supportive atmosphere, positive socialization and being part of the team is important for NGRNs to reduce anxiety and enhance job satisfaction (van Rooyen, Jordan, ten Ham‐Baloyi, & Caka, ). It has, however, been reported that NGRNs are concerned that asking too many questions may be perceived as annoying and give the image that they do not have enough knowledge (Murray, Sundin, & Cope, ). Several studies have also noticed the importance of gaining clinical competence through support from and collaboration with experienced colleagues (Lima et al, ; Numminen, Ruoppa, et al, ; Pasila et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The NGRNs included in this study have assessed that they need further training in nursing interventions in association with direct patient care. Recent studies have shown that NGRNs are afraid to make mistakes regarding medication (Halpin, Terry, & Curzio, ) and that the administration of medication is a cause of stress among NGRNs as they have deficient knowledge of different types of medication and their interactions (Murray et al, ). It is reported that 55% of NGRNs have made errors with medication leading to feelings of fear and horror as they realized they might have harmed a patient (Treiber & Jones, ).…”
Section: Discussionmentioning
confidence: 99%